Invasive and expansive plant species in Slovakian agrocoenoses - Májeková, Jana; Zaliberová, Marica (Biodiversity: Research and Conservation, 2008)
The distribution of invasive alien and expansive native vascular plant species in plant communities growing on fields in Slovakia was studied. Arable fields (cereals, perennial fodder crops, root, and stubbles) and 1-2-year abandoned fields were evaluated. The study was based on phytosociological data consisting of 486 relevés recorded in 2002-2008, from various parts of Slovakia. In the group of 371 vascular plant taxa recorded in the segetal communities (so-called weeds), 56 taxa are invasive or expansive species, representing 15% of total taxa. Among them, 21 taxa are invasive (10 neophytes and 11 archaeophytes), 10 are potentially invasive, 4 are frequently escaping from cultivation, 6 are occasionally escaping from cultivation, 5 species are naturalized, 8 are expansive native taxa, and 2 are data-deficient. The most frequent invasive or expansive weed species in the studied agrocoenoses were: Tripleurospermum perforatum, Cirsium arvense, and Veronica persica. Recorded species belong to 19 families, mostly to the Asteraceae, Chenopodiaceae, and Poaceae.